(untitled) (Journal of Economic Research & Business Administration, 2019)
The article examines the experience of the academic staff management as the main force for the implementation of the educational process in higher educational institutions of European countries. Comparative analysis of the key aspects of human resources management in universities of Europe, personnel selection, recruitment, employment and professional development has been made. The purpose of the study is to familiarize with the experience of the academic staff formation ways, which are involved in the educational process, the requirements for the academic staff, their pedagogical load, weekly working hours, selecting process of them and organization of the training programs, working conditions in European universities. During the research, the authors used common scientific methods and techniques like analysis, synthesis, comparison, and generalization of data with corresponding conclusions. According to the results of the study the practice of human resources management experience has difference between the countries of Europe due to the different level of socio-economic development of the country, financial capabilities of each University, and the mechanisms for the implementation of strategic plans. For example, Austrian universities select academic staff for vacancies in lower-level positions on an open basis, for associate-level positions on the basis of career growth, and University professors on the basis of a combination of these two factors. In some countries of the European Union, in particular Norway, Switzerland, Greece, Hungary, Slovenia, academic staff of higher education institutions are recognized as public servants by law, and this makes it possible to optimally address the issues of their long-term employment, favorable working conditions and wages. In Czech Republic, Poland, Slovakia and Hungary, the title of professor is appointed by the head of the country, while the Italian Ministry of Education, University and Research bases on a competitive evaluation committee decision. The practical significance of the study is that in the context of the Bologna process the successful experience and the best models of European country universities on the academic staff management can be applied in the higher education institutions of Kazakhstan taking into account the national characteristics of the country. It has positive effect on increasing competitiveness of the economy by training a high qualified, smart, and talent professionals.